Efek ekstrak etanol kulit dalam durian (durio zibethinus) terhadap Actinomyces sp. (Laporan Penelitian) - Jennifer Catry; Ade Prijanti Dwisaptarini; H.M. Bernard Ongki Iskandar (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Caries is a disease in the oral cavity that involves the hard tissue of the teeth, which is common in young and old people and causes pulpal necrosis. One of the treatments performed to treat pulpal necrosis is root canal treatment. Until now, research related to durian skin which is associated with antibacterial reactions against bacteria that cause root canal disease is still narrow. Objective: To assess the antibacterial effect of ethanol extract of skin durian on Actinomyces sp. as a root canal irrigant. Methods: True experimental design research was carried out using Actinomyces sp. bacteria were treated with concentrations of 35%, 30%, 25%, 20%, and 15% by microdilution method. Results: The ethanol extract of durian skin is the most effective in inhibiting the growth of Actinomyces sp. is 35% with an average colony yield of 0.2 x 106 CFU/ml. Conclusion: The ethanol extract of the durian rind which has the most effective antibacterial effect is at a concentration of 35%.